Factors influencing internal shariah audit effectiveness: evidence from Bahrain - Azam Abdelhakeem Khalid Ahmed (Tanjong Malim, 2019)
Factors influencing internal shariah audit effectiveness: evidence from Bahrain by Azam Abdelhakeem Khalid Ahmed